Glucocorticoids in myasthenia gravis – if, when, how, and how much?. (29th July 2014) - Hoffmann, S.; Kohler, S.; Ziegler, A.; Meisel, A.
<x xml:space="preserve">Abstract</x> Glucocorticoids (GC) are the most commonly used immune‐directed therapy in myasthenia gravis (MG). However, to date, GC have not proven their effectiveness in the setting of a randomized clinical trial that complies with currently accepted standards. The rationale for the use of GC in MG is the autoimmune nature of the disease, which is supported by consistent positive results from retrospective studies. Well‐defined recommendations for treatment of MG with GC are lacking and further hampered by inter‐ and intra‐individual differences in the disease course and responses to GC treatment. Uncertainties concerning GC treatment in MG encompass the indication for treatment initiation, exact dosage, dose adjustment in specific conditions (e.g., pregnancy, thymectomy), mode of tapering, and surveillance of adverse events (AE). This review illustrates the mode of action of GC in the treatment for MG, presents the currently available data on GC treatment in MG, and attempts to translate the currently available information into clinical recommendations.